Weight stigma amid pediatric healthcare providers: a cross-sectional survey study assessing the roles of weight controllability beliefs and blame - Taylor Dennison; Sarah Nutter; Nita Chauhan (BMC Pediatrics)
Abstract Background Weight stigma affects healthcare providers’ practice and contributes to poor patient outcomes. While it has been well-documented among providers of adult patients, research among providers of pediatric patients is limited and descriptive. The aim of this study was to answer the question: to what extent do pediatric healthcare professionals hold weight stigma towards patients and their parents, and what factors influence these attitudes? Methods An anonymous cross-sectional online survey was distributed from June-August 2023 to all healthcare workers, including providers-in-training, working with pediatric patients at a single centre in a province in central Canada. Participants who did not complete the survey, or who submitted it with excessive missing data, were removed. Primary outcome measures included weight stigma towards pediatric patients and their parents. Results 113 respondents were included. There was both a significant and positive direct effect of weight controllability beliefs on weight stigma towards parents (b = 0.58, 99% CI: 0.27, 0.89), as well as a significant and positive indirect effect, via blame (b = 0.33, 99% CI: 0.10, 0.61). Towards patients, there was a significant and positive indirect effect of weight controllability, via blame (b = 0.28, 99% CI: 0.08, 0.49). Conclusions Our findings highlight the importance of weight controllability beliefs in the stigma towards pediatric patients with higher body weights and their parents, and the ensuing blame that can occur when providers believe weight is within individual control. This work adds to the limited and descriptive weight stigma research on healthcare providers in pediatric healthcare settings.